Global Burden of Alzheimer's disease and other dementias in adults aged 65 years and older, 1991–2021: population-based study - Zhu Xiaopeng; Yu Jing; Lai Xia; Wang Xingsheng; Deng Juan; Long Yan; Li Baoshan (Frontiers in Public Health)
ObjectivesThis study aims to analyze the prevalence, impact, and disparities of Alzheimer's disease and other dementias (ADRD) among adults aged 65 years and older worldwide, across different regions and countries, spanning the years 1991–2021.MethodsGBD 2021 obtained data on dementia from vital registration systems, published scientific literature and surveys, and data from health-service encounters on deaths, excess mortality, prevalence, and incidence from 1991 to 2021, through systematic review and additional data-seeking efforts. Individuals aged ≥65 years from 21 regions and 204 countries and territories (Global Burden of Disease and Risk Factors Study 2021) from 1991 to 2021 were analyzed. Primary outcomes were ADRD related to aged ≥65 years age-standardized prevalence, deaths, disability-adjusted life years (DALYs), and average annual percentage change (AAPC), and the fractions of these metrics that were attributable to three risk factors (high BMI, high fasting glucose, and smoking) that met GBD.ResultsThe global mortality of ADRD among adults aged ≥65 years increased by 115%, from 6.5 (95% UI 1.5–18) per 100,000 population in 1991 to 14 (95% UI 3.5–37) per 100,000 population in 2021, with an Average Annual Percentage Change (AAPC) of 1.10% (95%CI 0.45%−1.76%). The prevalence of ADRD in adults aged ≥65 years increased by 160% between 1991 and 2021, from 18.7 (95%UI 14.9–23.2) million to 49 (95%UI 38.6–61.2) million. The aged ≥65 years age-standardized prevalence of ADRD in this age group increased from 11,977 (95%UI 9,438–14,935) per 100,000 population in 1991 to 12,124 (95%UI 9,489–15,204) per 100,000 population in 2021. The aged ≥65 years the number of prevalent persons was more significant among females than among males (males: from 6.2 (95%UI 4.8–7.8) million in 1991 to 17.2 (95%UI 13.4–21.6) million in 2021; women: from 12.5 (95%UI 10.0–15.4) million in 1991 to 31.7 (95%UI 25.1–39.6) million in 2021). In 2021, ADRD in adults aged ≥65 years caused 8.02 (95%UI 1.34–22.19) million deaths and 25.38 (95%UI 23.18–71.20) million DALYs attributable to dementia, and high BMI, high fasting glucose, and smoking remained modifiable risk factors in all risk factors.ConclusionsFrom 1991 to 2021, the worldwide prevalence of Alzheimer's disease and other dementias among adults aged 65 and above has increased by 1.6 times, largely driven by the expanding older adults. This escalating trend poses significant challenges to the global healthcare system in terms of both mortality rates and disability-adjusted life years. We recommend that standardized screening programmes be promoted globally, especially in high-risk areas and among high-risk populations, for early detection and intervention of the disease. Secondly, we recommend strengthening the management of risk factor elements.